EFL Pre-Service Teachers’ Challenges and Strategies in Implementing Kurikulum Merdeka During Teaching Practicum - Purnomo, Kristian Anggi; Yunika Upa (JADEs Journal of Academia in English Education, 2025)
This study aims to explore the challenges and strategies experienced by EFL pre-service teachers in implementing Kurikulum Merdeka during their teaching practicum, particularly in rural elementary schools in Landak Regency, Indonesia. The research was conducted in five rural elementary schools involving ten EFL pre-service teachers who were actively engaged in their practicum under the Kurikulum Merdeka framework. Using a qualitative case study approach, data were collected through questionnaires, semi-structured interviews, and document analysis. Thematic analysis was employed to interpret the qualitative data and identify recurring challenges and strategies. The findings revealed that pre-service teachers encountered several major challenges, including limited teaching resources and infrastructure, difficulties adapting to student-centered approaches, and struggles in designing flexible and authentic assessments aligned with the curriculum's principles. Despite these obstacles, the participants employed various strategies, including attending workshops on Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT), collaborating with senior teachers, and seeking additional learning resources independently. These strategies helped them adapt their teaching practices and improve their readiness to implement the curriculum. The study highlights the importance of institutional support, professional development, and mentorship in ensuring the successful implementation of Kurikulum Merdeka by pre-service teachers. It concludes that addressing these challenges is crucial for preparing competent English language educators and recommends further research into long-term impacts of curriculum implementation on teacher identity and student outcomes.